2019
DOI: 10.1146/annurev-linguistics-011718-012329
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Language Learning in Children

Abstract: Artificial language learning methods—in which learners are taught miniature constructed languages in a controlled laboratory setting—have become a valuable experimental tool for research on language development. These methods offer a complement to natural language acquisition data, allowing researchers to control both the input to learning and the learning environment. A large proportion of artificial language learning studies has aimed to understand the mechanisms of learning in infants. This review focuses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…In past work, ALL has corroborated or enhanced insights from natural language acquisition (Wonnacott, Newport, & Tanenhaus, 2008), language typology (Culbertson, Smolensky, & Legendre, 2012), and computational modeling (Schuler, Yang, & Newport, 2016), so we conclude that ALL can-and doesplay an important role in piecing together our understanding of learning biases. See Culbertson and Schuler (2019) and Morgan and Newport (1981) for further discussion of what ALL can tell us about language acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…In past work, ALL has corroborated or enhanced insights from natural language acquisition (Wonnacott, Newport, & Tanenhaus, 2008), language typology (Culbertson, Smolensky, & Legendre, 2012), and computational modeling (Schuler, Yang, & Newport, 2016), so we conclude that ALL can-and doesplay an important role in piecing together our understanding of learning biases. See Culbertson and Schuler (2019) and Morgan and Newport (1981) for further discussion of what ALL can tell us about language acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial language learning has a long history as a tool for studying learning in both adults and children (see e.g. Culbertson & Schuler, 2019 for review), and allows us to explore how learners deviate from their data during learning. To extend this technique to study the cycle of learning and use shown in Figure 1, we can simply connect up a series of participants, using the language (re)produced by one participant as the learning input for the next participant in a chain of transmission, meaning that any errors or innovations in learning can accumulate over 'generations' of transmission.…”
Section: Non-compositionality In Englishmentioning
confidence: 99%
“…Depictions of alien communication in film and literature often touch upon issues central to language evolution, and the potential challenge of speaking to aliens has often helped to frame linguistic research (Little, 2018). In empirical studies of langauge, especially those used in language evolution, many experiments use aliens explicitly to engage participants in the task of learning novel artifical languages to communicate with a naïve interlocutor (Kirby et al 2008;Culbertson and Schuler, 2019).…”
mentioning
confidence: 99%
“…Meanings range from simple and abstract (e.g., coloured shapes) to more concrete or complex (e.g., a child kicking a ball). Artificial language learning is often used to simulate the process of child language acquisition (Gómez andGerken, 2000, Culbertson andSchuler, 2019), or to compare how children learn artificial languages differently from adults (Hudson Kam andNewport, 2005, Folia et al 2010). These languages are often framed explicitly as 'alien', though the nonsense-words are constrained by the phonological rules of the participants' native language (e.g., for English, blick, napilu, but not *lbick, *ngipnu).…”
mentioning
confidence: 99%